Esophageal Pleural Fistula in Esophageal Squamous Cell Carcinoma: A Diagnostic Challenge - Salarieh, Naghmeh; Gholami, Roham; Soltani, Moslem; Askarian, Masoud; Ketabi Moghadam, Pardis (Asian Pacific Journal of Cancer Biology, 2023)
Esophageal pleural fistula (EPF) is a rare but serious complication of esophageal squamous cell carcinoma (ESCC), characterized by an abnormal communication between the esophagus and the pleural space. This abstract provides an overview of EPF in the context of ESCC, focusing on its etiology, clinical presentation, diagnosis, and treatment options. ESCC is a prevalent malignancy worldwide, particularly in regions with a high incidence of tobacco and alcohol consumption. As the tumor progresses, it can invade adjacent structures, including the pleura. The infiltration of the tumor into the pleural space may lead to the formation of an EPF. Patients with EPF often present with symptoms such as cough, dyspnea, chest pain, recurrent pneumonia, or subcutaneous emphysema. However, the clinical manifestations can vary widely, making the diagnosis challenging. Radiological imaging, including contrast-enhanced computed tomography (CT) scans and barium studies, plays a crucial role in detecting the presence and extent of the fistula. The management of EPF in ESCC involves a multidisciplinary approach. Treatment options depend on various factors, including the patient’s overall health status, tumor stage, and extent of the fistula. Conservative measures, such as nutritional support, antibiotics, and drainage of pleural effusion, may be employed in patients who are not surgical candidates. However, the definitive treatment for EPF is usually surgical intervention, which aims to resect the involved segment of the esophagus and repair the fistula. In some cases, palliative strategies, such as stenting or endoscopic interventions, may be considered to alleviate symptoms and improve quality of life. Through this article, we debate on a 47-year-old man presenting with esophageal fistula as the complication of esophageal squamous cell carcinoma. He has always been concerning about dysphagia, however endoscopic biopsies have been unsatisfying till now.